The Moderating Role of Information Technology in Improving the Values of Islamic Management Accounting Information Systems - Mellya Embun Baining; Amir, Amri; Achmad Hizazi; Enggar Diah Puspa Arum (LAA MAISYIR: Jurnal Ekonomi Islam, 2024)
In the context of Zakat Management Organisation (OPZ) in Indonesia, the management of zakat funds in accordance with the values of sharia management accounting information system becomes crucial, to maintain public trust. Management accounting information system in an organisation is related to the availability of management accounting information as a basis for decision making. There are several studies on management accounting, but the influence of contingency variables on the values of Sharia Management Accounting Information System (SIAMSy) has not been studied in more depth. This study aims to fill this gap by empirically examining the influence of environmental uncertainty, human resource competence, internal control, and Islamic organisational culture on SIAMSy values, as well as the moderating role of information technology in the relationship. This study uses primary data collected through questionnaires and interviews with OPZ in Jambi City, with data analysis conducted using a quantitative approach. The results showed that environmental uncertainty, HR competence, internal control, and Islamic organisational culture had a significant effect on increasing SIAMSy values. In addition, information technology proved unable to moderate the influence of contingency variables on SIAMSy. This research makes an important contribution to the development of a more effective and efficient management accounting information system, and offers recommendations for OPZ to increase SIAMSy values to improve the National Zakat Index (IZN).